2022
DOI: 10.1007/s11469-021-00733-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral intervention in dealing with Internet addiction among Arab teenagers in Israel

Abstract: The current study examines the effectiveness of a cognitive-behavioral intervention program for improving self-control and reducing Internet addiction among Arab adolescents in Israel. The study sample included 160 students who were 7th to 9th graders, recruited from eight schools in northern Israel. All participants exhibited high scores on a questionnaire indicating elevated symptoms of Internet addiction. Students were randomized to one of two groups: the experimental group underwent a systematic interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
7

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
0
11
0
7
Order By: Relevance
“…The most often utilized psychological treatment for Internet addiction is cognitive behavioral therapy (CBT), which is less intrusive than therapies for other addictive disorders. CBT methods for the treatment of Internet addiction in teenagers have been shown to be successful in lowering the symptoms of video game addiction in particular and Internet usage in general (134,135). The following are the primary evidence-based CBT techniques for treating Internet addiction in adolescents: identifying the advantages and disadvantages of using the Internet; enhancing self-awareness, environmental awareness, and awareness of others; identifying and comprehending the precursors that lead to compulsive Internet consumption (e.g., disconnection from certain applications, complex emotional state, environmental changes, and key events); developing emotional regulation and behavioral inhibition in relation to Internet access (e.g., calming methods and relaxing muscles and breathing exercises); learning and implementing time management tactics; improving interpersonal and social communication skills; and devoting time to hobbies such as art, sports, and dancing (136)(137)(138).…”
Section: Discussionmentioning
confidence: 99%
“…The most often utilized psychological treatment for Internet addiction is cognitive behavioral therapy (CBT), which is less intrusive than therapies for other addictive disorders. CBT methods for the treatment of Internet addiction in teenagers have been shown to be successful in lowering the symptoms of video game addiction in particular and Internet usage in general (134,135). The following are the primary evidence-based CBT techniques for treating Internet addiction in adolescents: identifying the advantages and disadvantages of using the Internet; enhancing self-awareness, environmental awareness, and awareness of others; identifying and comprehending the precursors that lead to compulsive Internet consumption (e.g., disconnection from certain applications, complex emotional state, environmental changes, and key events); developing emotional regulation and behavioral inhibition in relation to Internet access (e.g., calming methods and relaxing muscles and breathing exercises); learning and implementing time management tactics; improving interpersonal and social communication skills; and devoting time to hobbies such as art, sports, and dancing (136)(137)(138).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cognitive–behavioral treatments have the potential to improve self-control, depression, and anxiety and reduce symptoms of Internet addiction in the adolescent population. According to research [ 35 ], which applied cognitive–behavioral therapy for addictive behaviors among seventh to nineth graders, the experimental group had higher levels of self-control than the control group, indicating preliminary efficacy in reducing Internet addiction. Kim et al (2018) also revealed that participants’ addiction, depression, and anxiety scores were significantly lower than after group CBT intervention [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CBT is the most effective intervention for reducing Internet use and improving self-perception in chronic users, producing improvements in a short period that are maintained for at least six months [ 33 , 34 ]. This type of therapy works to reframe negative thoughts, assisting adolescents in giving a new sense to routine and problematic behaviors and motivating the creation of a more adaptive, goal-oriented routine [ 35 ] to improve symptoms of depression and anxiety. Second, family therapy aims to improve parent–adolescent communication and relationships and redirect adolescents’ psychological needs from the Internet and toward interactions and relationships with family members.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of the counseling approach must be accompanied by special techniques according to the problems to be handled by the counselor. According to Agbaria (2022), cognitive restructuring techniques in cognitive behavioral counseling can overcome adolescent problems related to internet addiction (online games and social media). Behavioral counseling with self-management techniques is also effective in helping counselors deal with teenage online game addiction (Wölfling & Dominick, 2022).…”
Section: Discussionmentioning
confidence: 99%